2018
DOI: 10.1111/aas.13178
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A4 gene polymorphism is correlated with individual consumption of sufentanil

Abstract: In summary, we found a correlation between CYP3A4 genetic polymorphism and sufentanil consumption. This might be helpful for optimizing the anesthesia strategies and reducing their side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
1
15
1
Order By: Relevance
“…Although, oxycodone (a 4,5‐epoxymorphinan) is O‐dealkylated by CYP2D6, its N‐dealkylation is catalyzed primarily by CYP3A4 (c.f., Drewes et al) . A single nucleotide polymorphism (CYP3A4*1G) is reported to affect the enzymatic activity of CYP3A4 and reduce plasma drug levels . Of high relevance to this study, humans heterozygous for the CYP3A4*1G allele exhibited lower intravenous self‐administration of sufentanil (a fentanyl derivate) for pain management .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Although, oxycodone (a 4,5‐epoxymorphinan) is O‐dealkylated by CYP2D6, its N‐dealkylation is catalyzed primarily by CYP3A4 (c.f., Drewes et al) . A single nucleotide polymorphism (CYP3A4*1G) is reported to affect the enzymatic activity of CYP3A4 and reduce plasma drug levels . Of high relevance to this study, humans heterozygous for the CYP3A4*1G allele exhibited lower intravenous self‐administration of sufentanil (a fentanyl derivate) for pain management .…”
Section: Discussionmentioning
confidence: 77%
“…A single nucleotide polymorphism (CYP3A4*1G) is reported to affect the enzymatic activity of CYP3A4 and reduce plasma drug levels . Of high relevance to this study, humans heterozygous for the CYP3A4*1G allele exhibited lower intravenous self‐administration of sufentanil (a fentanyl derivate) for pain management . Although it remains to be determined how polymorphisms in CYP3A4 might relate to the propensity to consume opioids in uninjured individuals, the rs4646440 and rs2242480 polymorphisms in CYP3A4 are associated with greater withdrawal severity during methadone maintenance therapy .…”
Section: Discussionmentioning
confidence: 92%
“…Sufentanil is oxidized and metabolized by CYP3A4. [7][8][9][10] Catechol-O-Methyltransferase (COMT) is catecholamine main metabolic enzymes in vivo and it is used to control body to produce dopamine, which is involved in sufentanil metabolism. 11 The μ-opioid receptor 1 (OPRM1) encodes opioid receptor.…”
Section: Introductionmentioning
confidence: 99%
“…A new multicenter, open-label, randomized controlled trial confirmed that RPCA is superior to pethidine for alleviating labor pain without serious adverse events [13]. Due to genetic polymorphisms, there are differences in not only opioid consumption but also in individual sensitivity to pain [26,27]. If the individual genetic polymorphism is identified before administering opioids, intravenous remifentanil analgesia should yield better satisfaction with labor pain relief.…”
Section: Discussionmentioning
confidence: 99%